Current perspectives on the benefits, risks, and limitations of noninvasive brain stimulation (NIBS) for post-stroke dysphagia. (3rd October 2021) - Cheng, Ivy; Hamdy, Shaheen
ABSTRACT: Introduction: Studies have shown that noninvasive brain stimulation (NIBS), including repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), can promote neuroplasticity, which is considered important for functional recovery of swallowing after stroke. Despite extensive studies on NIBS, there remains a gap between research and clinical practice. Areas covered: In this article, we update the current knowledge on the benefits and challenges of rTMS and tDCS for post-stroke dysphagia. We identify some key limitations of these techniques that hinder the translation from clinical trials to routine practice. Finally, we discuss the future of NIBS as a treatment for post-stroke dysphagia in real-world settings. Expert opinion: Current evidence suggests that rTMS and tDCS show promise as a treatment for post-stroke dysphagia. However, these techniques are limited by the response variability, uncertainty on the safety in patients with comorbidities and difficulties in clinical study designs. Such limitations call for further work to enhance their utility through individualized approaches. Despite this, the last decade has seen a growing acceptance toward these techniques among clinical personnel. As such, we advocate caution but support optimism that NIBS will gradually be recognized as a mainstream treatment approach for post-stroke dysphagia in the future.